Dyskeratosis congenita, bone marrow failure, and gastric adenocarcinoma: an insight into telomere biology - Sahoo, Nibedita; Padhi, Somanath; Patra, Susama; Mishra, Pritinanda; Kumar, Rajesh; Panigrahi, Manas Kumar (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Sahoo N, Padhi S, Patra S, Mishra P, Kumar R, Panigrahi MK. Dyskeratosiscongenita, bone marrow failure, and gastric adenocarcinoma: an insight into telomere biology. Turk J Gastroenterol 2017; 28: 319-21.